Entrepreneurial Model In The Community Muslim Entrepreneurs In Indonesia - Ahmad Fauzi (Iqtishodia: Jurnal Ekonomi Syariah, 2023)
The current development is that approximately 1.4 billion of the world's population live on less than USD 1 per day, and since 50% of the poorest people are in Muslim countries, one of the solutions is to increase successful Muslim entrepreneurs to be encouraged and able to color other Muslims. Therefore, this study aims to create a conceptual model through a literature review and descriptive-qualitative approach. It is used to determine the indicators of successful Muslim entrepreneurs and the expected factors needed to provide positive and significant effects. Meanwhile, four factors and indicators were identified, each of which is considered to influence successful Muslim entrepreneurs. Furthermore, the results obtained are conceptual papers and hypotheses that require testing to ensure their veracity. It was also used to generate new validated constructs for individuals and communities of Muslim entrepreneurs. Therefore, this conceptual model is expected to motivate new research in the future and has also been enhanced as a pioneer trying to build a model of successful Muslim entrepreneurs. Finally, a conceptual model was created that is an initial contribution to addressing poverty among the Muslim population in the world.